The polluters' paradox: Exploring the impact of green transition potential on carbon emissions in top ten emitters - Daghbagi Hamrouni; Zohra Kahouli; Radhouane Hasni; Imen Ouerghi (Center of Biomass & Renewable Energy (CBIORE), 2026)
Understanding the determinants of CO2emissions and the real possibilities for energy transition is essential to supporting sustainable growth, particularly for the world's ten largest emitters. These countries present a notable paradox: despite high economic complexity and efforts towards green transition, their emissions remain among the highest, revealing a persistent structural dependence on carbon-intensive activities and thus calling into question their effective capacity to sustainably reduce their emissions. This study fills a gap by simultaneously analyzing polluting specialisation and green transition potential using two indicators derived from economic complexity: the Brown Lock-In Index (BLI) and the Green Complexity Potential (GCP). The analysis, conducted on a panel of the ten largest CO2 emitters between 1999 and 2023 using FMOLS and PCSE estimators, shows that a carbon-intensive economic structure significantly increases emissions, while a higher green complexity potential contributes to their reduction. Furthermore, while economic growth and the use of non-renewable energies intensify environmental pressure, the consumption of renewable energies plays an important mitigating role. By highlighting the combined effect of polluting specialization and transition potential, this study offers decision-makers a structured understanding of the sources of their emissions and the real margins for transitioning to a low-carbon economy.